Conscientizar o trauma para descolonizar o inconsciente: experiências de um homem afro-indígena que é sujeito e objeto nesta ponte entre a antropologia e a psicanálise - Oliveira, Paulo Edison de (2023)
Contemporary western civilization is not racist! Contemporary Western civilization is being racist. It is necessary to believe in the movement of change, to have hope that we will leave a better world for the next generations and to end racism. The aim of this thesis is to problematize the method of producing academic knowledge based exclusively on Western references. Decolonial thinking is building bridges, giving voice to those who have been historically silent and daring to produce knowledge and/or questioning and/or dialogue between anthropology and psychoanalysis. In the search for a decolonial methodology, I carried out three fields of research. First, I interviewed middle-class black people from the city of São Paulo who are in a position of authority and are aware of racism and their condition as black or black. Second, using new technologies and the assumption of dialogue between the unconscious, I held two rounds of online conversations, the first round with black and white people to dialogue about racism. The second round with white people to dialogue about whiteness and privileges. Finally, the third field is my life story, experience and meanings when interviewing people. Despite the analysis of the interviews and conversation circles being produced by me, the idea of this writing is to record, from personal motivations, how the processes of psychic identification happened during the research. It is meta-research within research. A look at the subject that analyzes the object and at the same time is an object. To be subject and object is to talk about one's own history, the history of others and their intersections, the great history of the peoples we descend from and their crossings